THE THE DEVELOPMENT OF PRIVILEGED COMMUNICATION RULE UNDER THE MALAYSIAN EVIDENCE ACT 1950 - Mohamad Ismail Bin Mohamad Yunus (Indonesia Private Law Review, 2022)
It is observed that if there is a civil dispute between the parties, they may try to settle it outside court, for example, by using the process of alternative dispute resolution. When there is actual cause of action between the parties, the settlement might be done through negotiations. If such negotiation settlement fails, they might bring the matter to the court and if any party wants to admit the damaging statements made during the negotiation, these statements or communications are privileged as “without prejudice communication” under s. 23 of the Malaysian Evidence Act 1950.The issue is whether the law requires some changes and new mechanism to adapt ‘without prejudice’ privilege at present. Is the rule absolute? What are the exceptions that have been ruled out by the Court which can be considered as the limitations of the rule? The objective of this paper is to discuss the matters